Impact of feed optimization and extension intervention on productive and reproductive performance in commercial dairy farms of urban areas in the eastern region of Ethiopia - Senbeta, Ewonetu Kebede; Zeleke, Negassi Ameha; Dingidie, Gemechu Taffa (Indian Journal of Dairy Science, 2021)
This study aimed at assessing the husbandry practices and evaluates the impact of feed optimization on productive performances and reproductive disorders of dairy cows. The study was conducted in purposefully selected Harar and Dire Dawa cities on 76 and 16 dairy farms respectively. Data were collected by use of semi-structured questionnaires and focused group discussion. Commonly used feeds were analyzed for their nutrition and standardized to the cows’ requirement. Milk yield was recorded every day for four consecutive months while milk composition was evaluated every month. Data analysis was done by SPSS, one-way ANOVA and t-Test. The pre-intervention results showed that farmers from small, medium and large-scale farms fed cows on low concentrate quantity of 3.76, 4.61 and 5.84Kg/day, respectively. The quantity of concentrate supplementation per cow per day was significantly different (p<0.0001) among farm-scales. Cows maintained under different farm-scales produced low milk yields (9.57-13.07 litter). Cows from large-scale farms significantly produced milk with lower fat (P<0.0006) whereas small-scale farms produced milk with lower protein and milk urea (P<0.0001). All milking cows maintained in small, medium and large farm-scales were highly affected by oestrus (44.45%), placenta retention (35.19%) and repeat breeding (20.37%). The technical intervention of feed optimization boosted daily milk yield from 17.64 to 27.44%, enhanced most milk components except fat and milk urea, and reduced the incidence of all observed reproductive disorders. Finally, this study concluded that regular technical advice and feed optimization improved milk production and reduced reproductive disorders of dairy farmers at the three farm scales.